1999
DOI: 10.1046/j.1365-2222.1999.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil activation following TDI bronchial challenges to the airway secretion from subjects with TDI‐induced asthma

Abstract: SummaryBackground The immunopathological mechanism for occupational asthma induced by toluene diisocyanate (TDI) remains to be further clari®ed. There have been few reports suggesting involvement of neutrophils in inducing bronchoconstriction after TDI inhalation. Objectives To further understand the role of neutrophils in the pathogenesis of TDIinduced asthma. Materials and methods Eight TDI-induced asthmatic subjects were classi®ed as group I, and ®ve exposed workers who had complained of work-related sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 33 publications
(40 reference statements)
2
54
1
1
Order By: Relevance
“…Its levels are commonly increased in neutrophilic asthma and TDI-OA [9]. Although no significant increases in IL-8 after MDI exposure were noted in the airway secretions of MDI-OA patients in the present study, sputum IL-8 levels were highly correlated with sputum eosinophil counts and ECP levels, which may contribute to eosinophilic activation.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Its levels are commonly increased in neutrophilic asthma and TDI-OA [9]. Although no significant increases in IL-8 after MDI exposure were noted in the airway secretions of MDI-OA patients in the present study, sputum IL-8 levels were highly correlated with sputum eosinophil counts and ECP levels, which may contribute to eosinophilic activation.…”
Section: Discussioncontrasting
confidence: 65%
“…In our previous study, serum-specific IgE and IgG antibodies were shown to be increased in some MDI-induced occupational asthma (MDI-OA) patients, of which specific IgG antibodies were more associated with work-related respiratory symptoms (WRRS) [7]. Activated neutrophils have also been suggested to play a role in the pathogenic mechanisms of toluene diisocyanate-induced occupational asthma (TDI-OA) [8,9]. However, these cellular mechanisms involved have not been investigated in MDI-OA.…”
Section: Introductionmentioning
confidence: 98%
“…22,23 Sustained release of these inflammatory products enhances neutrophil-induced inflammation in the airway and subsequent airway hyperreactivity. 24,25 As we previously reported, 20 neutrophils may contribute to bronchoconstriction induced by TDI. Furthermore, the number of eosinophils in the BAL fluid increased in our TDIinduced asthma model, although the magnitude was less than that seen with neutrophils.…”
Section: Discussionmentioning
confidence: 69%
“…3,4,20 In TDI-induced asthma in human subjects, neutrophilia in BAL fluid has been found in association with asthmatic reactions induced by isocyanate challenge. 21 Neutrophils could be an important source of proinflammatory cytokines and proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…5 As in other forms of asthma, inflammatory changes are found in the airways of patients with TDI asthma, along with eosinophils, T cells, and collagen deposition as well as the typical range of cytokines associated with asthma. [6][7][8] When T-cell clones were derived from the airways of patients with TDI asthma, the majority were CD8 + and expressed IL-5 and IFN-γ, 9 suggesting similarities with the T-cell response seen in patients with atopic asthma. 10 However, when patients with TDI asthma underwent bronchial challenge, they showed a more marked neutrophil response 8 than would be expected in corresponding pollen or house dust mite challenges.…”
mentioning
confidence: 98%